2016
DOI: 10.1002/anie.201602504
|View full text |Cite
|
Sign up to set email alerts
|

Rechargeable Room‐Temperature Na–CO2 Batteries

Abstract: Developing rechargeable Na-CO2 batteries is significant for energy conversion and utilization of CO2 . However, the reported batteries in pure CO2 atmosphere are non-rechargeable with limited discharge capacity of 200 mAh g(-1) . Herein, we realized the rechargeability of a Na-CO2 battery, with the proposed and demonstrated reversible reaction of 3 CO2 +4 Na↔2 Na2 CO3 +C. The battery consists of a Na anode, an ether-based electrolyte, and a designed cathode with electrolyte-treated multi-wall carbon nanotubes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
191
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 222 publications
(198 citation statements)
references
References 27 publications
6
191
1
Order By: Relevance
“…[50] The reversible formation and decomposition of Na 2 CO 3 was detected by in situ Raman, ex situ X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS). Meanwhile, the reversibility of CO 2 was also verified by measuring the evolved gas during the charging process.…”
Section: Na-co 2 Batteriesmentioning
confidence: 99%
See 2 more Smart Citations
“…[50] The reversible formation and decomposition of Na 2 CO 3 was detected by in situ Raman, ex situ X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS). Meanwhile, the reversibility of CO 2 was also verified by measuring the evolved gas during the charging process.…”
Section: Na-co 2 Batteriesmentioning
confidence: 99%
“…[50,59] Both DFT calculations and Raman and Fourier transform infrared (FTIR) results suggest that the porous structure and activated surface of the a-MCNTs facilitated the adsorption of CO 2 , the storage of discharge product, and the cathode reactions (Figure 8). Therefore, a low overpotential of 1.39 V is observed for the cells with a-MCNT cathodes compared with that with nonactivated MCNT cathode (2.04 V) (Figure 8f), which is a preliminary indication of the effectiveness of a-MCNT cathodes.…”
Section: Wwwadvsustainsyscommentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15] The stability limit of the carbon electrode in Li-O 2 batteries has been reported to be ≈3.5 V (vs Li/Li + ). [22,23] In 2013, Hartmann et al reported a room-temperature Na-O 2 battery that could be cycled with a much lower charge overpotential (η < 200 mV) and better rechargeability (Coulombic efficiency [CE] > 90%) than otherwise identical Li-O 2 batteries (η > 1 V and CE < 80%). [16,17] Parallel to the pursuit of rechargeable Li-O 2 batteries, research interests in aprotic sodium-air (Na-O 2 ) batteries have surged recently because of their relatively high theoretical specific energy and particularly their uncompromised round-trip efficiency.…”
Section: Doi: 101002/adma201606816mentioning
confidence: 99%
“…For example, in most of Li + and Na + batteries carbonate-based electrolytes are widely used; but these electrolytes have the drawbacks of potential leakage, inflammability and volatility, which create major safety issue and reduce lifetime, (particularly at high temperatures). [201][202][203][204] To get rid of all these difficulties, development of efficient solid electrolyte interfacial materials is highly demanded to act as novel medium for Li/ Na-based batteries. [198,199] So, to avoid these problems, surface chemistry of the electrodes must be optimized to obtain an enhanced electrochemical performance of the device.…”
Section: Zwitterion Materials For Lithium Ion Batteriesmentioning
confidence: 99%